Cultural significance of the Jatiroto sugar factory official house in Stasiun Street Lumajang Regency (ARTEKS : Jurnal Teknik Arsitektur, 2021)
The assessment of cultural significance is important to the processes involved in the determination of building preservation policies. The cultural significance is mostly invisible or intangible in a cultural heritage building and contained in the form of value or meaning which are sometimes misinterpreted and this means it is possible to judge a building as worthy or unworthy to be preserved for the interests of the past, present, and future through the evaluation its importance. Moreover, some important elements are usually contained in a cultural heritage building which can be excavated through their cultural significance. This research was, therefore, conducted to determine the cultural significance of residential buildings in the Jatiroto Sugar Factory area complex at Lumajang Regency, East Java to be used in formulating policies required to preserve the structures as a cultural heritage for the benefit of future generations. This involved the use of the descriptive method to describe the situation in the field while the weighted evaluative method was applied to evaluate the cultural significance value of the building and its elements. The results were used as the criteria to determine the cultural significance of the official house of the Jatiroto Sugar Factory which can be applied as the reference to formulate the cultural significance criteria for similar cultural heritage buildings in other locations.
Keywords: Cultural significance; Jatiroto sugar factory official house; Lumajang Regency